Production of polyhydroxyalkanoates on waste frying oil employing selected Halomonas strains - Pernicova, Iva; Kucera, Dan; Nebesarova, Jana; Kalina, Michal; Novackova, Ivana; Koller, Martin; Obruca, Stanislav (Bioresource technology, 2019)
The aim of this work was to study the potential of selected Halomonas species for conversion of waste frying oil into polyhydroxyalkanoates (PHA). In total nine Halomonas strains were experimentally screened for their capability of PHA production. Among them, Halomonas neptunia and Halomonas hydrothermalis were identified as potent PHA producers. Initial concentration of NaCl was identified as parameter influencing PHA yields as well as molecular weight of the polymer. In addition, H. hydrothermalis was capable of biosynthesis of a copolymer of 3-hydroxybutyrate and 3-hydroxyvalerate P(3HB-co-3HV). When valerate was utilized as a precursor, the 3HV fraction in the copolymer reached high values of 50.15 mol.%. PHA production on lipid substrates by Halomonas has not been reported so far. Bearing in mind all the positive aspects of employing extremophiles in industrial biotechnology, H. hydrothermalis seems to be a very interesting halophilic strain for production of PHA using lipid substrates.
Keywords: Polyesters; biotechnologie; 3-Hydroxybutyric Acid; Halomonas; polyestery; Biotechnology; polyhydroxyalkanoáty; kyselina 3-hydroxymáselná; Polyhydroxyalkanoates